English Language Education and Feminist Pedagogy: Reflections of a Tertiary Level Teacher - Sinha, M. (University of Jaffna, 2025)
Locating feminist pedagogy in the context of empowerment and social justice alongside ‘experience’ as a crucial concept for knowledge production, this paper emerges out of my reflections as a teacher of English Language and Literature at a central university in India. Here “Feminist Pedagogy” can be defined as a process from a gender perspective to make the classroom a democratic space. The context of English in a postcolonial country like India is both aspirational and hierarchical. Universities have become melting pots of the diverse Indian society due to the transformative capacity of education and the policy of reservation but difference in the quality of schooling and language education bring huge disparity in terms of the English language capability of students for academic purposes. While teaching different courses in TESL (Teaching English as a Second Language), over the last two decades, I have tried to bring notions of identity, difference, marginalization through feminist texts that I use in my classes. These articles also raise issues of marginality from the location of caste, class, sexuality, race etc. to create a conducive learning context. The effort is to help the students to incorporate the notions of respect, mutuality and community building through various classroom practices, projects and discussions. My analysis is based on my involvement in teaching a course, “Language Teaching through Media,” for a semester in 2019 as part of a programme called Post Graduate Diploma for Teaching in English (PGDTE). I wish to particularly discuss the journey of two students who in the language of pedagogic practices could easily be labelled “reticent”, and “weak” but they finally turned in a project work which was greatly appreciated by the class and fetched them a good grade. The conscious choice of selecting texts, careful grouping of students and individual discussions with those who needed an extra support helped me immensely again in 2022 for PGDTE, but this time over two semesters where I taught two courses “Interpretation of Literature” (Semester 1) and “Teaching of Literature” (Semester 2). In both these courses I had included texts highlighting discrimination based on caste, class, gender, sexuality, race etc. which brought in a nuanced understanding of difference. Caste, community and sexuality became very interesting analytical tools and students by the second semester gradually formed new friendships and developed a new understanding of many of the ideological questions and improved their language skills. With the comparison of these two classes as case studies I will try to demonstrate that the English classroom can become a space of inclusive learning and ethical knowledge production with Feminist Pedagogy as a critical approach. My research attempts to deal with the following questions: How could I rework the notion of academic “merit” and the hierarchy based on it through my classroom practices foregrounding the notion of identity and community? What changes are possible when students are involved in the selection, discussion and assessment process by becoming a learning community rather than remaining individual students? What could be some possible ways of bringing in empathy and ethics in the classroom for social justice?
Keywords: Feminist pedagogy; English language education; Experience; Difference; Social justice